The Analysis of Traditional Menu Promotion, Case Study: The City of Pagar Alam - Pelliyezer Karo Karo; Samuel Hamonangan; Agus Setiawan (Politeknik Pariwisata Makassar, 2023)
This study compares traditional menu promotion efforts' expectations and reality in Pagar Alam, South Sumatra. The focus of attention of food and beverage industry players is customers and competitors. By generating and offering value to their customers, food and beverage industry players can bind a customer, a food and beverage player who has succeeded in presenting superior value. In order to achieve this goal, every industry player must be able to produce and deliver the goods and services desired by consumers, in this case, tourists, according to the needs and desires of these tourists. The data analysis method uses Important Performance Analysis (IPA) on primary data obtained from 83 consumer respondents. The results showed strategies to improve product branding to introduce and improve the specific menu products of natural fences so that tourists more widely knew them. The results showed that labeling was in quadrant D (low expectation and perception values) at an IPA value of 5.40.